2015
DOI: 10.4103/1119-3077.151776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic and sonic scaling on surfaces of tooth-colored restorative materials: An in vitro study

Abstract: On the basis of these results, the repolishing of restoration surfaces is strongly recommended after dental scalings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…It was ob-served that both prophylactic polishing procedures significantly roughened the surfaces of all tested groups; however, air polishing device more adversely affected the surface roughness than ultrasonic scaling, especially in Fuji IX GP Extra and Fuji II LC groups. Similar to our findings Erdilek et al 22 showed that glass ionomer restorative that they tested exhibited the roughest surfaces, while the flowable resin composite had the smoothest surfaces. In addition to this literature, Lin et al 12 revealed that glass ionomers were more prone to surface alterations than resin composites.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It was ob-served that both prophylactic polishing procedures significantly roughened the surfaces of all tested groups; however, air polishing device more adversely affected the surface roughness than ultrasonic scaling, especially in Fuji IX GP Extra and Fuji II LC groups. Similar to our findings Erdilek et al 22 showed that glass ionomer restorative that they tested exhibited the roughest surfaces, while the flowable resin composite had the smoothest surfaces. In addition to this literature, Lin et al 12 revealed that glass ionomers were more prone to surface alterations than resin composites.…”
supporting
confidence: 92%
“…10 It could be supposed that scaling procedures may damage the marginal integrity of cervical restorations, thus leading to the development of tooth sensitivity and adversely affecting the longevity and esthetic appearance of the restorations. 22 In our in vitro study it was seen that, ultrasonic scaling with or without air polishing device resulted in significant increases in surface roughness. However the effect of air polishing device was higher.…”
mentioning
confidence: 70%
“…The color change of composite resins occurs over time depending on internal and external factors. Surface roughness and irregularities cause bacterial plaque retention and superficial staining, whereas subsurface and internal discolorations occur because of resin matrix composition including its conversion rate and water absorption after polymerization (29,30). Restorative materials are exposed to changing temperatures, humidity and mechanical forces constantly in the oral environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic scaling has been shown to be less time-consuming and easier to use than hand instrumentation [14,15], although both methods yield similar results [16,17]. Ultrasonic scaling allows effective disruption of biofilms without traumatizing surrounding structures [18].…”
Section: Introductionmentioning
confidence: 99%